Francis Lymburner interviewed by Hazel de Berg in the Hazel de Berg collection - Lymburner, Francis, 1916-1972.; De Berg, Hazel, 1913-1984. (1965)
Lymburner speaks about his English experience; his methods; the subject of his paintings; his drawings; defining his style.
Also available online
Transcript available (6 p.)
Keywords: Lymburner, Francis, -- 1916-1972 -- Interviews; Painters -- Australia -- Interviews